Bevacizumab Improves Quality of Life in Patients with Recurrent Glioblastoma. (18th September 2011) - Nagpal, Seema; Harsh, Griffith; Recht, Lawrence
Abstract : Objective . To quantify the benefits in survival and quality of life in patients receiving bevacizumab (BEV) for recurrent glioblastoma (GBM). Methods . This is a retrospective study of 40 adult patients with recurrent GBM treated between 2005 and 2009 at a single institution. All patients had initial treatment with surgery, radiation, and concurrent temozolomide, then monthly temozolomide. Over 250 charts were screened. Sufficient data was available for 20 patients treated with BEV and 20 patients who did not receive BEV at the time of recurrence. The independent living score (ILS), designed to reward long-term independent survival, was calculated for each patient. Results . The mean ILS was nearly double in the BEV group compared to the No-BEV group (15.0 versus 8.2, P = 0.002, t -test). Two months after initiation of therapy, the median steroid dose dropped by over 90% in patients treated with BEV, but doubled in the NoBEV group. Median survival from the time of recurrence was significantly affected: 10.6 months in the BEV group versus 4.2 months (P < 0.001, log rank survival) in the NoBEV group. Conclusions . BEV increases independent living and lengthens overall survival after GBM recurrence. Reduction in steroid dose may contribute to prolonged independence.